2022
DOI: 10.1016/j.brs.2022.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Anodic and symmetric biphasic pulses enlarge the therapeutic window in deep brain stimulation for essential tremor

Abstract: Background: Since the inception of DBS, cathodic pulses have been used. Objective: To investigate the effect of anodic and symmetric biphasic pulses on the therapeutic window (TW) in essential tremor (ET) patients. Methods: A randomized, doubled-blinded, cross-over design was used to test the effect of cathodic, anodic and symmetric biphasic pulses (cathode-first and anode-first) on the TW in an acute clinical setting. TW was defined as the difference between the minimal stimulation amplitude provoking side ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…No adverse events were reported, but we are cautious with our conclusions considering the small sample size. In line with previous results ( 5 , 6 ), we documented that higher stimulation amplitudes are necessary when stimulating biphasically (symmetric active biphasic pulse with anodic phase first and no interphase gap) to obtain equivalent clinical responses as with cathodic stimulation. This increase in amplitude and the two active phases in symmetric biphasic pulses (active anodic and cathodic phase) theoretically entails an increase of energy consumption compared to the cathodic pulse.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No adverse events were reported, but we are cautious with our conclusions considering the small sample size. In line with previous results ( 5 , 6 ), we documented that higher stimulation amplitudes are necessary when stimulating biphasically (symmetric active biphasic pulse with anodic phase first and no interphase gap) to obtain equivalent clinical responses as with cathodic stimulation. This increase in amplitude and the two active phases in symmetric biphasic pulses (active anodic and cathodic phase) theoretically entails an increase of energy consumption compared to the cathodic pulse.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in stimulation amplitude can render a (sometimes only temporary) tremor suppression with the risk of causing stimulation-induced ataxia ( 4 ). Symmetric biphasic pulses have been proposed as a solution to solve the problem of narrow therapeutic windows as these biphasic pulses have shown to mainly increase the side effect threshold compared to cathodic pulses ( 5 ). Furthermore, after three hours of symmetric biphasic stimulation, patients had equivalent tremor control but less stimulation-induced ataxia as with cathodic stimulation ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, active recharge produces higher side effect thresholds, suggesting that the utility of chronic active recharge paradigms (available on rechargeable implantable pulse generators) could provide an enhanced stimulation paradigm in patients with narrow therapeutic windows. Similarly, Boogers et al recently evaluated side effect thresholds between different stimulation paradigms and found that biphasic stimulation pulses had a wider therapeutic window and higher side effect threshold compared to traditional stimulation, and that that these differences were most pronounced for anodic-first biphasic pulses (Boogers et al, 2022 ). Our findings are consistent with the findings from Boogers et al Future studies with larger cohorts involving different stimulation patterns are needed to further assess optimal stimulation patterns and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To further optimize patient outcomes after DBS and minimize its side effects, a variety of stimulation delivery strategies such as novel stimulation waveform shapes (Foutz and McIntyre, 2010 ; Hofmann et al, 2011 ), different pulse-width (Daniel et al, 2019 ; Dayal et al, 2020 ), frequency (Khoo et al, 2014 ; Su et al, 2018 ), and charge balancing systems have been used (De Jesus et al, 2018 ; Boogers et al, 2022 ). In particular, charge balancing is crucial to prevent net charge accumulation in the tissues and subsequent neural damage (Lilly et al, 1955 ), especially when delivering high-frequency stimulation as DBS (Piallat et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation